"Absence has not abated your love":1 the nostalgia for an idealized aristocracy in The Castle of Lindenberg during the Romantic era. Issue 4 (1st October 2016) - Gerard, W. B.
Abstract: During the late eighteenth and early nineteenth centuries, a popular thirst for sensation wed to historic anxieties about political and social unrest infused gothic literature and art. This article examines the texts of nine abridgements of Matthew Lewis's novel The Monk (1795) between 1798 and 1823 as projecting the trials of sympathetic aristocratic characters who encounter natural and supernatural disruptions that are depicted in their thirteen illustrations; in these texts, the disruptions represent threats to the established order through the inappropriate exercise of power. The combination of text and illustration in these abridgements (primarily chapbooks), variously entitled The Castle of Lindenberg, Raymond and Agnes, and The Bleeding Nun, reflect a nostalgic desire for leadership by a threatened, idealized aristocracy that combines traditional heroic characteristics of romances with Enlightenment values of reason and compassion.